2019
DOI: 10.1016/j.bpj.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Conformation of Wild-Type Bacterial Lipopolysaccharide Layers at Air-Water Interfaces

Abstract: The outer membrane of Gram-negative bacteria is of great scientific interest because it mediates the action of antimicrobial agents. The membrane surface is composed of lipopolysaccharide (LPS) molecules with negatively charged oligosaccharide headgroups. To a certain fraction, LPSs additionally display linear polysaccharides termed O-side chains (OSCs). Structural studies on bacterial outer surfaces models, based on LPS monolayers at air-water interfaces, have so far dealt only with rough mutant LPSs lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 54 publications
2
22
1
Order By: Relevance
“…S2). In particular, ρ X-ray ∼ 15 × 10 −4 nm −2 of the OS-layer suggested that water is expelled, which is inconsistent with neutron reflectometry experiments on supported LPS layers showing that the hydration of the inner and outer cores ranges from 40 to 80 vol% (Clifton et al, 2013;Rodriguez-Loureiro et al, 2018;Micciulla et al, 2019).…”
Section: Multi-scale Scattering Modelcontrasting
confidence: 57%
See 2 more Smart Citations
“…S2). In particular, ρ X-ray ∼ 15 × 10 −4 nm −2 of the OS-layer suggested that water is expelled, which is inconsistent with neutron reflectometry experiments on supported LPS layers showing that the hydration of the inner and outer cores ranges from 40 to 80 vol% (Clifton et al, 2013;Rodriguez-Loureiro et al, 2018;Micciulla et al, 2019).…”
Section: Multi-scale Scattering Modelcontrasting
confidence: 57%
“…The here applied scattering contribution estimates are based on the latest experimental and computational reports on E. coli, including isolated cell components. Specifically, we used compositional and structural information about E. coli and its cell-wall (Neidhardt et al, 1990;Seltmann & Holst, 2002;Schwarz-Linek et al, 2015); the cytoplasmic space and its components (Zimmerman & Trach, 1991;Tweeddale et al, 1998;Maharjan & Ferenci, 2003;Bennett et al, 2009;Guo et al, 2012;Lebedev et al, 2015); the bacterial ultrastructure (Hobot et al, 1984;Beveridge, 1999;Matias et al, 2003); the lipid membrane composition and structure (De Siervo, 1969;Oursel et al, 2007;Lohner et al, 2008;Pandit & Klauda, 2012;Kučerka et al, 2012;Kučerka et al, 2015;Leber et al, 2018); the LPS specifics (Heinrichs et al, 1998;Müller-Loennies et al, 2003;Kučerka et al, 2008;Kim et al, 2016;Rodriguez-Loureiro et al, 2018;Micciulla et al, 2019); the periplasmic space (Burge et al, 1977;Labischinski et al, 1991;Pink et al, 2000;Gan et al, 2008); and the external bacterial components (Yamashita et al, 1998;Whitfield & Roberts, 1999;Stukalov et al, 2008;Turner et al, 2012). All this information has been condensed into SLDs ρ, which are summarized in The benefit of this detailed description becomes clear considering the ability of SANS to nullify or enhance contrast for a given molecular entity, depending on the applied H 2 O/D 2 O ratio.…”
Section: Overall Scattering Contributions and Compositional Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…20 X-ray diffraction on monolayers of similar LPS species showed a much lower compressibility for monolayers with Ca 2+ than those with Na + . 21 Furthermore, monolayers of E. coli LPS revealed significantly smaller lipid areas in the presence of 20 mM Ca 2+ with 100 mM NaCl, compared to 100 mM NaCl alone or no ions, 22 indicating that the type of ion species has a larger influence on the monolayer structure than the ionic strength alone. The neutron scattering density profiles of Kucerka This condensing effect is manifested through smaller lipid areas, decreased tail mobility, and increased molecular packing.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the previous section, the main limitation of the slab model is the description of (vertically, along z) diffuse layers. This can be the case, among several others, of polymer brushes deposited onto surfaces [30][31][32] or of inhomogeneous systems [33], for which a description through a limited number of well defined layers might fail. As reported in the cited literature, these systems can be modeled by a combination of slabs, for the homogeneous regions (if any) of the sample, and by functional distributions, describing volume fraction profiles, for the inhomogeneous ones.…”
Section: Functional Component Groupsmentioning
confidence: 99%